Penyelesaian analitik persamaan diferensial parsial simultan linier dar' proses transport suatu zat yang mengalami reaksi bertingkat order satu pada medium terbuka dengan sumber titik seketika (Instantaneous Point Sourc - Perpustakaan UGM, i-lib ([Yogyakarta] : Center For Food and Nutritions Studies Gadjah Mada University, 1999)
ABSTRACS Transport process of a substance that undergoes sequential first order reaction in open medium occurs in engineering and environmental analysis. In environmental analysis, this problem occurs M the problem of transport of chemicals and radioactive contaminans which undergo reaction process that produces other substances that still have contamination hazard properties. These substances disperse to the environtnient with their own transport properties. Thus the overall contamination analysis must deal with simultaneous partial linier differential equation of each substances. Numerical solution of this problem suffers the limitation of computer memory and the difficulty of boundary condition formulation because.of the fact that environmental medium must be treat as an open medium. Analytical solution can be obtained with succesive general Fourier and Laplace tranform. The solution is still in integral forms and must be solved by numerical integration. However numerical integration does not need very large computer memory space compared with direct numerical solutions. The method has been succesfully demonstrated to calculate concentration of radioactive contaminan and its daughter that undergo sequential decay process in a river stream as time and position function.